A qualitative study about immigrant workers' perceptions of their working conditions in Spain. Issue 11 (28th May 2009) - Ahonen, E Q; Porthé, V; Vázquez, M L; García, A M; López-Jacob, M J; Ruiz-Frutos, C; Ronda-Pérez, E; Benach, J; Benavides, F G; ,
Abstract : Background: Spain has recently become an inward migration country. Little is known about the occupational health of immigrant workers. This study aimed to explore the perceptions that immigrant workers in Spain had of their working conditions. Methods: Qualitative, exploratory, descriptive study. Criterion sampling. Data collected between September 2006 and May 2007 through semi-structured focus groups and individual interviews, with a topic guide. One hundred and fifty-eight immigrant workers (90 men/68 women) from Colombia (n = 21), Morocco (n = 39), sub-Saharan Africa (n = 29), Romania (n = 44) and Ecuador (n = 25), who were authorised (documented) or unauthorised (undocumented) residents in five medium to large cities in Spain. Results: Participants described poor working conditions, low pay and health hazards. Perception of hazards appeared to be related to gender and job sector. Informants were highly segregated into jobs by sex, however, so this issue will need further exploration. Undocumented workers described poorer conditions than documented workers, which they attributed to their documentation status. Documented participants also felt vulnerable because of their immigrant status. Informants believed that deficient language skills, non-transferability of their education and training and, most of all, their immigrant status and economic need left them with little choice but to work under poor conditions. Conclusions: The occupational health needs of immigrant workers must be addressed at the job level, while improving the enforcement of existing health and safety regulations. The roles that documentation status and economic need played in these informants' work experiences should be considered and how these may influence health outcomes.